PGAweb: A Web Server for Bacterial Pan-Genome Analysis - Chen, Xinyu; Zhang, Yadong; Zhang, Zhewen; Zhao, Yongbing; Sun, Chen; Yang, Ming; Wang, Jinyue; Liu, Qian; Zhang, Baohua; Chen, Meili; Yu, Jun; Wu, Jiayan; et al. (Frontiers in Microbiology, 2018)
An astronomical increase in microbial genome data in recent years has led to strong demand for bioinformatic tools for pan-genome analysis within and across species. Here, we present PGAweb, a user-friendly, web-based tool for bacterial pan-genome analysis, which is composed of two main pan-genome analysis modules, PGAP and PGAP-X. PGAweb provides key interactive and customizable functions that include orthologous clustering, pan-genome profiling, sequence variation and evolution analysis, and functional classification. PGAweb presents features of genomic structural dynamics and sequence diversity with different visualization methods that are helpful for intuitively understanding the dynamics and evolution of bacterial genomes. PGAweb has an intuitive interface with one-click setting of parameters and is freely available at http://PGAweb.vlcc.cn/.